Strawberry shortcake and the butterfly garden - Curry, Kelli (New York : Grosset & Dunlap, 2005)
Strawberry shortcake and her friends visit a butterfly garden.
Keywords: Butterflies -- Fiction; Butterfly garden -- Fiction